A Guide to Innovative Public-Private Partnerships: Utilizing the Resources of the Private Sector for the Public Good - Cellucci, Thomas A. (Government Institutes, 2011)
Congress is expected to announce that new practices are to be adopted across the federal sector which will incite new and innovative partnerships between the public and private sectors. In A Guide to Innovative Public Private Partnerships: Utilizing the Resources of the Private Sector for the Public Good author Thomas A. Cellucci introduces these new procedures and how both private entrepreneurs and government managers can use them most effectively. This book enables organizations in both the private and public sectors to develop and execute efficient and effective business partnerships. Detailed requirements and market potentials are developed which would help entice the private sector to use its own resources to develop products and services without delay and at minimal cost to taxpayers. The book starts from basic principle of partnerships, develops the concept of commercialization-based public-private partnerships, and provides templates, potential marketing tools, and real-world examples to prove the effectiveness of this shift in how government will work in the future. This is a 'must read' for anyone interested in doing business with the government as well as government leaders who are being forced to trim budgets and show genuine value in their agencies.